Torsion of an accessory spleen - Yasser Mustafa; Ayham Khaddam; Hamid Alkhaled (Elsevier, 2021)
An accessory spleen is commonly an incidental detection. Torsion of an accessory spleen is an uncommon reason of abdominal pain. We report the case of a 12-year-old female was admitted with acute abdominal pain that began 5 days earlier. In the face of the acute pain, a laparotomy was necessary. At laparotomy, the patient was found to have twisted and infarction of an accessory spleen with a long pedicle ending near the splenic hilum. The procedure was a removal of the accessory wandering spleen and the evolution was favorable.